THE RHETORICAL PROCEEDINGS OF JOVANA JOKSIMOVIĆ OBSERVED THROUGH THE ELEMENTS OF NUŠIĆ'S "RHETORIC" DURING THE PRESENTATION OF THE MORNING PROGRAM ON COMMERCIAL TELEVISION CHANNELS - Perišić, Nikola; Ficovic, Maja (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Jovana Joksimović is a journalist and presenter who has devoted most of her career to hosting the same format of shows, which is the morning program, and she has been working on this type of television format for almost 20 years. It is for this reason that she can be considered one of the most experienced presenters in Serbia when it comes to this type of program and the host who has been continuously engaged in the form of morning programs in Serbia for the longest time. During her career, she worked on three different commercial television stations, namely: Pink, Prva and K1. It should be noted that on Pink and Prva she often hosted the program together with Srđan Predojević. Because of all the mentioned subject of the work is Jovana Joksimović and her rhetorical qualities when leading the morning program. The basic hypothesis from which the work is based is that regardless of the different commercial television channels on which she worked, Jovana Joksimović is prone to the same rhetorical actions, as well as that she often interrupts her interlocutors during the conversation she leads and interrupts them. Those hypotheses are confirmed because her rhetorical actions are not in accordance with what Nušić gives in his "Rhetoric" as a certain type of recommendation for desirable rhetorical behavior. More precisely, Jovana Joksimović's journalistic expression is dominated by an illogical and incongruous presence, which has the consequence that there is no proper order during the interviews she does in her television program.
Keywords: morning program, Jovana Joksimović, rhetorical analysis, Nušić's rhetoric, commercial television channels